Enhancing Aircraft Maintenance: Safety Management Systems and Capability Building for Optimal MRO Business Performance - Rosita, Ai; Rahayu, Agus; Disman, Disman; Furqon, Chairul (Universitas Pendidikan Indonesia, 2023)
The aeronautics sector, including aircraft construction, parts supply or maintenance of aircraft parts, and repair and modification services, is currently one of the most dynamic industries in the world. The business performance of aircraft maintenance companies is highly dependent on the Safety Management System (SMS) and Capability Building (CB). This research is a synthesis formed integrative based on various previous research literature modified by researchers. The population in this study were company leaders or parties representing them in private and state-owned Maintenance, Repair, and Operations (MRO) companies, totaling 119, with a sample of 91 respondents. This research was verification research with an explanatory survey. Data analysis used the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach through the SmartPLS software. We found that MRO business performance is influenced by SMS and CB in aircraft maintenance service companies in Indonesia. CB mediated the effect of SMS on Business Performance in aircraft maintenance service companies in Indonesia. MRO business performance can be further improved with intervention from CB based on SMS integration. SMS was so integrated with CB that SMS could not develop without CB, and vice versa. One aspect that needed to continue to develop here was an assessment related to identifying accident risks in the SMS, which was integrated with various maintenance and overhauls in the CB. Keywords: Capability Building; MRO business performance; Safety Management System; Indonesian aviation sector.